Faktor-faktor yang Berhubungan dengan Kejadian Stunting pada Anak Balita - Nyimas Elsa Octa Aditia; Mitra Mitra; Aldiga Rienarti Abidin; Yuyun Priwahyuni; Christine Vita Gloria Purba (Jurnal Kesehatan Komunitas, 2023)
Stunting is a condition in which a child experiences growth disorders, resulting in a height that exceeds his age due to long-term dietary deficiencies. In 2021 Pekanbaru City was designated as a stunting focus location, totaling 15 urban villages with 303 stunting toddlers. This study aimed to determine the factors associated with stunting in children under five in Pekanbaru City in 2022. This type of research is quantitative analytic observational with a case-control design. The sample in the case group was stunted children under five, while the sample for the control group was children under five who were not stunted. The sample size for the case and control groups was 73 children under five, so the overall sample size was 146 children under five. The sampling technique used stratified random sampling at the integrated service center level. Data analysis was univariate and bivariate with a chi-square test. The results showed that exclusive breastfeeding (OR = 10,247), quality of complementary feeding (OR = 9,362), Infectious Diseases (OR = 4,1940, Mother's Knowledge (OR = 9,4410, and parenting patterns (OR = 10,065) associated with stunting. This study concludes that not exclusively breastfeeding, poor quality complementary feeding, presence of infectious diseases, low maternal knowledge, and suboptimal parenting have more risk for stunting in children under five. Public health center in order to provide information and education to the public regarding the risk factors for stunting.